Pathological fixation on shared beliefs: a review and bibliometric analysis of extreme, overvalued and delusion-like beliefs - Kristinsdottir, Kolbrun; Freestone, Mark; Underwood, Alan; Ebner, Julia (Frontiers in Psychiatry, 2025)
IntroductionAs researchers, practitioners, and policymakers highlight the changing landscape of security concerns, the growing domestic terrorist threat of radicalised lone actors cannot be overlooked. Extreme, overvalued and delusion-like beliefs are one piece of the puzzle, as adherence to shared extreme beliefs and conspiracy theories has become increasingly concerning in recent years. While interest and awareness have grown, there is a notable lack of consistency in conceptualisation and terminology across disciplines. A bibliometric analysis helped highlight existing focus areas across disciplines, current gaps and opportunities for future research.MethodologyThe Web of Science Core Collection was searched to identify publications on extreme overvalued beliefs, overvalued ideas, delusion-like beliefs, extreme beliefs, extremist beliefs, radical beliefs and strongly held ideas from January 2005 to September 2025. Trends in publications, dates and contributing countries were explored, and all results were uploaded to VOSviewer. A map based on bibliographic data focused on a keyword co-occurrence analysis was then generated and analysed separately for each concept in the search, and then combined to explore research focus in medicine and social sciences.ResultsThe majority of publications were from the United States, followed by England, Australia and Canada. There was a gradual increase in publications from 2005, a spike in 2015 and a notably increased focus since 2020. Co-occurring keywords with the strongest links were different for the concepts searched, but overlapped significantly between overvalued and delusion-like beliefs and on extreme beliefs and radical beliefs. The focus was also different in psychiatry, psychology, neuroscience and medicine compared to social science disciplines (law, sociology, philosophy, anthropology and criminology).DiscussionThis bibliometric review presents current knowledge, limitations, gaps, and recommendations for future studies on extreme, overvalued, and delusion-like beliefs. The review highlighted significant blurring of concepts between extreme, overvalued, and delusion-like beliefs and strongly held ideas that were striated along disciplinary lines. A need for greater consensus on the definitions and overlap of these terms was identified and discussed. By clarifying conceptual ambiguities, this review provides a foundation for developing cross-disciplinary consensus in threat assessment.